Diversity of herbal medicine in Mamasa District, West Sulawesi, Indonesia - ELIS TAMBARU; RESTI URA’; MUSTIKA TUWO (Society for Indonesian Biodiversity, 2023)
Abstract. Tambaru E, Ura’ R, Tuwo M. 2023. Diversity of herbal medicine in Mamasa District, West Sulawesi, Indonesia. Biodiversitas 24: 2013-2022. This study aimed to identify the species of traditional medicinal plants, the parts processed as medicine and the processing methods of the plants used in traditional medicine. This research was conducted in Mellangkenapadang Village and Paladan Village, Sesenapadang District, Mamasa Regency. This research method was descriptive exploratory. Qualitative data collection was carried out using the cruising method. Sampling of medicinal plants in the site was carried out using the Participatory Rural Appraisal method, an assessment process involving active roles of the community. The results showed that the number of medicinal plants growing in Mellangkenapadang Village and Paladan Village, Sesenapadang District, Mamasa Regency were 49 species belonging to, 30 families, the most widely used being Asteraceae, and 22 orders, the most widely used being Solanales. The number of medicinal plant species used in Mellangkenapadang Village was 46 species. The most frequently used plant was guava (93.33%) and the lowest pumpkin, pineapple, spoon leaf, and airplant (3.33%). Meanwhile, in Paladan Village, 43 species were used; the most frequently used was painted nettle (96.67%) and the least were airplant and galangal (3.33%). The most widely used plant part as traditional medicine was leaf (59.18%) and the least used were stems (2.04%) and seeds (2.04%). The processing of medicinal plants was mostly boiling (55.10%) and the least burning (2.04%). Medicinal plant knowledge needs to be preserved for the younger generation so that it can be used sustainably in the future. This can be done by conserving biodiversity and preserving the plant's genetic material for pharmaceutical development.